The writer's way - Rawlins, Jack 1946-; Metzger, Stephen 1954-. (Boston, MA Wadsworth, 2012)
Writers learn best when inspired by compelling reasons to write, aided by examples and reinforced by immediate personal rewards. With sound advice offered in a supportive tone, this book leads you through the writing process, from the importance of understanding your audience to pre-writing to polishing the final draft. You'll learn why good writers ask of their writing, "Will this work?" You'll also learn how to ensure that - with practice and revision - your answer will be "yes."--COVER.
Pt. 1. Introduction to writing -- Learning to write -- What makes writing effective? -- Writing in school : An introduction -- Pt. 2. Planning and drafting -- Choosing topics and getting started -- Thesis, purpose, and audience -- Style and tone -- Organization : Mapping, outlining, and abstracting -- Pt. 4. Modes of writing -- Personal writing -- Writing to inform -- Writing an argument, stage 1 : Thinking it through -- Writing an argument, stage 2 : Selling the case -- Pt. 5. Academic writing -- Research -- Using sources -- The academic research paper -- Pt. 6. A collection of good writing.
Includes indexes.
Includes bibliographical references and indexes.
Keywords: Authorship